Overdose following initiation of naltrexone and buprenorphine medication treatment for opioid use disorder in a United States commercially insured cohort. (1st July 2019) - Morgan, Jake R.; Schackman, Bruce R.; Weinstein, Zoe M.; Walley, Alexander Y.; Linas, Benjamin P.
Highlights: The opioid overdose crisis is deadly, but medication treatment is uncommon. The real-world comparative effectiveness of medication treatments is unknown. Buprenorphine therapy significantly reduced the risk of opioid related overdose. Overdose risk on naltrexone was not significantly different from no treatment. Abstract: Background and aims: Despite the growing opioid overdose crisis, medication treatment for opioid use disorder remains uncommon. The comparative effectiveness of buprenorphine and naltrexone treatment in reducing overdose and the comparative risks of discontinuing treatment in the real world, remain uncertain. Our aim was to examine the effectiveness of medications for opioid use disorder in preventing opioid-related overdose. Design: Retrospective cohort study Setting: United States. Patients: 46, 846 commercially insured individuals diagnosed with opioid use disorder and initiating medication treatment between 2010 and 2016. Measurements: Opioid-related overdose identified by International Classification of Diseases, Ninth and Tenth Revisions. Findings: In our sample, 1386 individuals were prescribed extended-release injectable naltrexone (median filled prescriptions = 9 months), 7782 were prescribed oral naltrexone (5 months), and 40, 441 were prescribed buprenorphine (19 months) at least once during follow-up. Individuals receiving buprenorphine therapy were at significantly reduced risk of opioid-related overdose compared to no treatment (adjusted hazard ratio (HR) = 0.40, 95% CI 0.35−0.46), while a significant association was not observed in extended-release injectable (HR = 0.74, 95% CI 0.42–1.31) or oral (HR = 0.93, 95% CI 0.71–1.22) naltrexone. We found no association with opioid overdose within four weeks of discontinuation of any medication. Conclusion: Among commercially-insured patients who initiate medications for opioid use disorder, buprenorphine, but not naltrexone, was associated with lower risk of overdose during active treatment compared to post-discontinuation. More research is needed to understand the benefits and risks unique to each treatment option to better tailor therapies to patients with opioid use disorder.